2005
DOI: 10.1302/0301-620x.87b8.15886
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin EP4 receptor agonist augments fixation of hydroxyapatite-coated implants in a rat model of osteoporosis

Abstract: The reduced stability of hydroxyapatite (HA)-coated implants in osteopenic conditions is considered to be a major problem. We therefore developed a model of a boosted cementless implantation in osteopenic rats.Twelve-week-old rats were either ovariectomised (OVX) or sham-operated (SO), and after 24 weeks plain or HA-coated implants were inserted. They were treated with either a prostaglandin EP4 receptor agonist (ONO-4819) or saline for one month. The EP4 agonist considerably improved the osteoporosis in the O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…The push-out force required to loosen the CaP-coated implant was approximately 3-fold higher compared with that for the control implants. These results corroborate earlier findings with plasmasprayed CaP-coated implants under osteoporotic conditions (Hara et al, 1999;Rocca et al, 2001;Hayashi et al, 2005). The histological difference in trabecular bone response adjacent to the CaP-implants was significant at 8 wks in our study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The push-out force required to loosen the CaP-coated implant was approximately 3-fold higher compared with that for the control implants. These results corroborate earlier findings with plasmasprayed CaP-coated implants under osteoporotic conditions (Hara et al, 1999;Rocca et al, 2001;Hayashi et al, 2005). The histological difference in trabecular bone response adjacent to the CaP-implants was significant at 8 wks in our study.…”
Section: Discussionsupporting
confidence: 93%
“…a significant role in the biomechanical fixation of implants (Hara et al, 1999;Hayashi et al, 2005). Conversely, it must be emphasized that some authors failed to show significant %BIC of CaP-coated implants in osteoporotic conditions (Vidigal et al, 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both types of osseointegration have potential applications, however in vivo studies are required to clarify the most suitable type of implant depending on the site of implantation (considering the mechanical load and the type of bone in need of repair) as well as the associated pathological conditions such as osteoporosis. Despite some limitations regarding the mechanical properties of porous apatite ceramics, the excellent osteoconductivity of HA coatings and the possibility of associating bioactive molecules (such as proteins, aminoacids, antibiotics, growth factors, anticancer and anti-osteoporosis drugs) to calcium phosphate indicate the potential advantages of the use of this type of coating especially in osteopenic bone repair [77,78]. On the other hand, the osseoinductive properties of SiO 2 -coated Ti implants (as described in our study) and their ability to promote angiogenesis and enhance neocartilage formation [73], can provide other important applications in implantology, especially for repairing bones at sites where mechanical strength is of lesser importance.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several studies using the agonist ONO--4819 have demonstrated a variety of anabolic effects, such as stimulation of osteoblast differentiation 214,215 , increased cortical bone formation in response to mechanical loading 216 , and accelerated cortical bone repair after femoral drill--hole injury 217 . Furthermore, ONO--4819 can also improve fixation of hydroxyapatite (HA)--coated implants in OVX rats by increasing the osteoconductivity of the HA coating and strengthening the bone--implant attachment 218 . 31 However, despite their anabolic effects, EP4 agonists also have drawbacks.…”
Section: Synthetic Ep4 Receptor Agonistsmentioning
confidence: 99%